Psychological safety: a qualitative study on coach and athlete perceptions - Cooke, M.; Paradis, K. F.; Sharp, L. A.; Woods, D.; Sarkar, M. (International Sport Coaching Journal, 2025)
Aims: The concept of psychological safety has received growing interest within a sport context in recent years. Despite a small but growing body of literature, there is still a lack of conceptual clarity, and thus research is needed to gain a better understanding of how psychological safety manifests in sport. Existing literature suggests psychological safety may allow for positive outcomes in various sport settings. As this may be of interest to many coaches and sporting organisations, a deeper evidence base will prove beneficial for further support to this claim. The aim of the current study was to garner conceptual clarity by gathering coach and athlete perceptions of psychological safety in high-performance pathway sport environments. Methods: Qualitative findings of six focus groups with coaches (two focus groups) and athletes (four focus groups) were comprised of four sports (association football, boxing, field hockey, and swimming). A total of 25 participants included 18 athletes (Mage = 19.6 years; Mexperience = 10.6 years) and seven coaches (Mage = 45 years; Mexperience = 19.6 years) who discussed psychological safety within their high-performance pathway sport environment. Focus groups lasted from 36 to 78 minutes (Mlength = 56 min). Qualitative content analysis was utilised to categorise themes identified from the focus groups. Findings: Findings offer a conceptualisation of the defining attributes (e.g., freedom to speak freely and raise issues), antecedents (e.g., positional competition, selection, and deselection), and outcomes (e.g., positive climate and enjoyment of sport) of psychological safety in sport settings. One of the key takeaways within the findings suggests that psychological safety in a sport context may manifest in a dual process, namely on-field (e.g., the freedom to take risks) and off-field (e.g., the freedom to speak freely and raise issues).